2018
DOI: 10.1021/acs.jpcc.8b07062
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Boron Nitride/Blue Phosphorene Heterostructure as a Promising Anode Material for Li/Na-Ion Batteries

Abstract: Blue phosphorene (blue-P), an allotrope of black phosphorene, is prone to oxidize under ambient conditions, which significantly hinders its incorporation in anode for Li/Na ion batteries (LIBs/NIBs). Combining blue-P and hexagonal boron nitride (h-BN) together to construct h-BN/blue-P heterostructure (BN/P) can break the limitation of the restricted properties of blue-P. By means of first-principles computations, we explored the potential of using BN/P as anode material for LIBs/NIBs. Our computations show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 52 publications
3
51
0
Order By: Relevance
“…Recently, there are a few theoretical investigation proposals that blue phosphorene (blue‐P), an allotrope of BP, also has great potential for LIB anode and suffers the same degeneration problem with BP. Recent theoretical calculation studies suggested that heterostructure blue‐P, including blue‐P/borophene, [ 89 ] blue‐P/graphene, [ 90 ] blue‐P/g‐C 3 N, [ 91 ] blue‐P/BN, [ 92 ] blue‐P/NbS 2 , [ 93 ] and blue‐P/TaS 2 , [ 94 ] are also very auspicious candidates as anode materials for LIBs. Among, blue‐P/borophene heterostructure presented an impressive high theoretical capacity of 1019 mA h g −1 , demonstrating the great potential of heterostructure materials applied as anode for LIBs.…”
Section: The Electrochemical Performance Of Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there are a few theoretical investigation proposals that blue phosphorene (blue‐P), an allotrope of BP, also has great potential for LIB anode and suffers the same degeneration problem with BP. Recent theoretical calculation studies suggested that heterostructure blue‐P, including blue‐P/borophene, [ 89 ] blue‐P/graphene, [ 90 ] blue‐P/g‐C 3 N, [ 91 ] blue‐P/BN, [ 92 ] blue‐P/NbS 2 , [ 93 ] and blue‐P/TaS 2 , [ 94 ] are also very auspicious candidates as anode materials for LIBs. Among, blue‐P/borophene heterostructure presented an impressive high theoretical capacity of 1019 mA h g −1 , demonstrating the great potential of heterostructure materials applied as anode for LIBs.…”
Section: The Electrochemical Performance Of Heterostructuresmentioning
confidence: 99%
“…[ 140 ] The recent theoretical studies also demonstrated the superiorities of h‐BN/phosphorene heterostructure and h‐BN/blue‐P heterostructure. [ 87,92 ] The design of heterostructure contained P‐based active materials will be inspirable to the development of anode materials for alkali metal ion batteries.…”
Section: The Electrochemical Performance Of Heterostructuresmentioning
confidence: 99%
“…2 The effects of doping, [3][4][5] functionalization, [6][7][8][9] and heterostructure formation, [10][11][12][13][14][15] including external stimuli such as strain and electric field, on the electronic and magnetic properties of BlueP are known from first-principles calculations, indicating that it is a promising 2D material. Various investigations have explored the potential in nanoelectronic devices, 16 photodetectors, 17 energy storage, 15,[18][19][20][21] gas sensors, [22][23][24] and superconductors. 25 While BlueP can be grown by molecular beam epitaxy on the Au(111) surface, 26,27 defects are inevitable during synthesis of 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Other graphene‐like transition metal dichalcogenides (TMDCs) and transition metal dicarbides (MXenes) have also been widely studied in LIBs . Besides monolayer 2D materials, heterostructures consisting of vertically stacked bilayer different 2D materials, such as h‐BN/black phosphorene and h‐BN/blue phosphorene, can exhibit excellent anode performances for LIBs/NIBs as well, which expands the potential of 2D materials as anode for LIBs/NIBs. In short, it is highly desirable to search for new 2D anode materials for high‐performance LIBs/NIBs.…”
Section: Introductionmentioning
confidence: 99%